Survival time of Phytophthora species in peat-reduced growing media under different storage conditions - Fabricio Fabián Soliz Santander; Janett Riebesehl (Journal für Kulturpflanzen)
In horticulture, the ecologically urgent switch to peat-free or peat-reduced growing media is a complex and challenging issue. Substrates should not only give the optimal chemical conditions for growing plant cultures but also be safe from soil-borne pathogens. One of the most destructive group of pathogens is the oomycete genus of Phytophthora, which can pose significant risks to plant nurseries. Commonly, these oomycetes remain latent in substrates until the proper conditions come to infect the plants. So far, little research has been done on the survival time of this oomycete genus in potentially new culture media.